Open-loop amplitude-modulation Kelvin probe force microscopy operated in single-pass PeakForce tapping mode - Stan, Gheorghe; Namboodiri, Pradeep (Beilstein Journal of Nanotechnology, 2021)
The open-loop (OL) variant of Kelvin probe force microscopy (KPFM) provides access to the voltage response of the electrostatic interaction between a conductive atomic force microscopy (AFM) probe and the investigated sample. The measured response can be analyzed a posteriori, modeled, and interpreted to include various contributions from the probe geometry and imaged features of the sample. In contrast to this, the currently implemented closed-loop (CL) variants of KPFM, either amplitude-modulation (AM) or frequency-modulation (FM), solely report on their final product in terms of the tip–sample contact potential difference. In ambient atmosphere, both CL AM-KPFM and CL FM-KPFM work at their best during the lift part of a two-pass scanning mode to avoid the direct contact with the surface of the sample. In this work, a new OL AM-KPFM mode was implemented in the single-pass scan of the PeakForce Tapping (PFT) mode. The topographical and electrical components were combined in a single pass by applying the electrical modulation only in between the PFT tip–sample contacts, when the AFM probe separates from the sample. In this way, any contact and tunneling discharges are avoided and, yet, the location of the measured electrical tip–sample interaction is directly affixed to the topography rendered by the mechanical PFT modulation at each tap. Furthermore, because the detailed response of the cantilever to the bias stimulation was recorded, it was possible to analyze and separate an average contribution of the cantilever to the determined local contact potential difference between the AFM probe and the imaged sample. The removal of this unwanted contribution greatly improved the accuracy of the AM-KPFM measurements to the level of the FM-KPFM counterpart.
Keywords: electrostatic interaction; Kelvin probe force microscopy; open loop; surface potential

(untitled) - Nonnenmacher, M.; O’Boyle, M. P.; Wickramasinghe, H. K. (Appl. Phys. Lett., 1991)

(untitled) - Kikukawa, A.; Hosaka, S.; Imura, R. (Appl. Phys. Lett., 1995)

(untitled) - Tanimoto, M.; Vatel, O. (J. Vac. Sci. Technol., B: Microelectron. Nanometer Struct.–Process., Meas., Phenom., 1996)

(untitled) - Abraham, D. W.; Williams, C.; Slinkman, J.; Wickramasinghe, H. K. (J. Vac. Sci. Technol., B: Microelectron. Nanometer Struct.–Process., Meas., Phenom., 1991)

(untitled) - Fujiwara, I.; Kojima, S.; Seto, J. (Jpn. J. Appl. Phys., 1996)

(untitled) - Gonzalez, J. F.; Somoza, A. M.; Palacios-Lidón, E. (Phys. Chem. Chem. Phys., 2017)

(untitled) - Lubarsky, G.; Shikler, R.; Ashkenasy, N.; Rosenwaks, Y. (J. Vac. Sci. Technol., B: Microelectron. Nanometer Struct.–Process., Meas., Phenom., 2002)

(untitled) - Shikler, R.; Meoded, T.; Fried, N.; Rosenwaks, Y. (Appl. Phys. Lett., 1999)

(untitled) - Loppacher, C.; Zerweck, U.; Teich, S.; Beyreuther, E.; Otto, T.; Grafström, S.; Eng, L. M. (Nanotechnology, 2005)

(untitled) - Schumacher, Z.; Miyahara, Y.; Spielhofer, A.; Grutter, P. (Phys. Rev. Appl., 2016)

(untitled) - Ishii, H.; Hayashi, N.; Ito, E.; Washizu, Y.; Sugi, K.; Kimura, Y.; Niwano, M.; Ouchi, Y.; Seki, K. (Phys. Status Solidi A, 2004)

(untitled) - Hoppe, H.; Glatzel, T.; Niggemann, M.; Hinsch, A.; Lux-Steiner, M. C.; Sariciftci, N. S. (Nano Lett., 2005)

(untitled) - Palermo, V.; Palma, M.; Samorì, P. (Adv. Mater. (Weinheim, Ger.), 2006)

(untitled) - Kalinin, S. V.; Bonnell, D. A. (Phys. Rev. B, 2001)

(untitled) - Shvebelman, M. M.; Agronin, A. G.; Urenski, R. P.; Rosenwaks, Y.; Rosenman, G. I. (Nano Lett., 2002)

(untitled) - Son, J. Y.; Kim, B. G.; Kim, C. H.; Cho, J. H. (Appl. Phys. Lett., 2004)

(untitled) - Leung, C.; Kinns, H.; Hoogenboom, B. W.; Howorka, S.; Mesquida, P. (Nano Lett., 2009)

(untitled) - Park, J.; Yang, J.; Lee, G.; Lee, C. Y.; Na, S.; Lee, S. W.; Haam, S.; Huh, Y.-M.; Yoon, D. S.; Eom, K.; Kwon, T. (ACS Nano, 2011)

(untitled) - Sinensky, A. K.; Belcher, A. M. (Nat. Nanotechnol., 2007)

(untitled) - Sorokina, K. L.; Tolstikhina, A. L. (Crystallogr. Rep., 2004)

Scanning Probe Microscopy - Glatzel, T.; Lux-Steiner, M. C.; Strassburg, E.; Boag, A.; Rosenwaks, Y. (Principles of Kelvin Probe Force Microscopy, 2007)

(untitled) - Melitz, W.; Shen, J.; Kummel, A. C.; Lee, S. (Surf. Sci. Rep., 2011)

Kelvin Probe Force Microscopy - Sadewasser, S.; Glatzel, T. (Springer Berlin, 2012)

(untitled) - Collins, L.; Kilpatrick, J. I.; Kalinin, S. V.; Rodriguez, B. J. (Rep. Prog. Phys., 2018)

(untitled) - Glatzel, T.; Sadewasser, S.; Lux-Steiner, M. C. (Appl. Surf. Sci., 2003)

(untitled) - Kikukawa, A.; Hosaka, S.; Imura, R. (Appl. Phys. Lett., 1995)

(untitled) - Kitamura, S.; Iwatsuki, M. (Appl. Phys. Lett., 1998)

(untitled) - Zerweck, U.; Loppacher, C.; Otto, T.; Grafström, S.; Eng, L. M. (Phys. Rev. B, 2005)

(untitled) - Coffey, D. C.; Ginger, D. S. (Nat. Mater., 2006)

(untitled) - Giridharagopal, R.; Rayermann, G. E.; Shao, G.; Moore, D. T.; Reid, O. G.; Tillack, A. F.; Masiello, D. J.; Ginger, D. S. (Nano Lett., 2012)

(untitled) - Murawski, J.; Graupner, T.; Milde, P.; Raupach, R.; Zerweck-Trogisch, U.; Eng, L. M. (J. Phys. D: Appl. Phys., 2015)

(untitled) - Araki, K.; Ie, Y.; Aso, Y.; Ohoyama, H.; Matsumoto, T. (Commun. Phys., 2019)

(untitled) - Collins, L.; Ahmadi, M.; Wu, T.; Hu, B.; Kalinin, S. V.; Jesse, S. (ACS Nano, 2017)

(untitled) - Takeuchi, O.; Ohrai, Y.; Yoshida, S.; Shigekawa, H. (Jpn. J. Appl. Phys., 2007)

(untitled) - Collins, L.; Belianinov, A.; Somnath, S.; Balke, N.; Kalinin, S. V.; Jesse, S. (Sci. Rep., 2016)

(untitled) - Stan, G. (Nanotechnology, 2020)

(untitled) - Guo, S.; Kalinin, S. V.; Jesse, S. (Appl. Phys. Lett., 2012)

(untitled) - Guo, S.; Kalinin, S. V.; Jesse, S. (Nanotechnology, 2012)

(untitled) - Collins, L.; Kilpatrick, J. I.; Weber, S. A. L.; Tselev, A.; Vlassiouk, I. V.; Ivanov, I. N.; Jesse, S.; Kalinin, S. V.; Rodriguez, B. J. (Nanotechnology, 2013)

(untitled) - Borgani, R.; Forchheimer, D.; Bergqvist, J.; Thorén, P.-A.; Inganäs, O.; Haviland, D. B. (Appl. Phys. Lett., 2014)

(untitled) - Kobayashi, N.; Asakawa, H.; Fukuma, T. (Rev. Sci. Instrum., 2012)

(untitled) - Kilpatrick, J. I.; Collins, L.; Weber, S. A. L.; Rodriguez, B. J. (Rev. Sci. Instrum., 2018)

(untitled) - Collins, L.; Kilpatrick, J. I.; Vlassiouk, I. V.; Tselev, A.; Weber, S. A. L.; Jesse, S.; Kalinin, S. V.; Rodriguez, B. J. (Appl. Phys. Lett., 2014)

(untitled) - Belianinov, A.; Kalinin, S. V.; Jesse, S. (Nat. Commun., 2015)

(untitled) - Collins, L.; Belianinov, A.; Somnath, S.; Rodriguez, B. J.; Balke, N.; Kalinin, S. V.; Jesse, S. (Nanotechnology, 2016)

(untitled) - Collins, L.; Ahmadi, M.; Qin, J.; Liu, Y.; Ovchinnikova, O. S.; Hu, B.; Jesse, S.; Kalinin, S. V. (Nanotechnology, 2018)

(untitled) - Elias, G.; Glatzel, T.; Meyer, E.; Schwarzman, A.; Boag, A.; Rosenwaks, Y. (Beilstein J. Nanotechnol., 2011)

(untitled) - Ziegler, D.; Stemmer, A. (Nanotechnology, 2011)

(untitled) - Girard, P.; Ramonda, M.; Saluel, D. (J. Vac. Sci. Technol., B: Microelectron. Nanometer Struct.–Process., Meas., Phenom., 2002)

(untitled) - Cohen, G.; Halpern, E.; Nanayakkara, S. U.; Luther, J. M.; Held, C.; Bennewitz, R.; Boag, A.; Rosenwaks, Y. (Nanotechnology, 2013)

(untitled) - Jacobs, H. O.; Leuchtmann, P.; Homan, O. J.; Stemmer, A. (J. Appl. Phys., 1998)

(untitled) - Strassburg, E.; Boag, A.; Rosenwaks, Y. (Rev. Sci. Instrum., 2005)

(untitled) - Machleidt, T.; Sparrer, E.; Kapusi, D.; Franke, K.-H. (Meas. Sci. Technol., 2009)

(untitled) - Xu, J.; Wu, Y.; Li, W.; Xu, J. (Nanotechnology, 2017)

(untitled) - Sadeghi, A.; Baratoff, A.; Ghasemi, S. A.; Goedecker, S.; Glatzel, T.; Kawai, S.; Meyer, E. (Phys. Rev. B, 2012)

Quantitative mechanical property mapping at the nanoscale with PeakForce QNM; Bruker Application Note #128 - Pittenger, B.; Erina, N.; Su, C.

Simultaneous Electrical and Mechanical Property Mapping at the Nanoscale with PeakForce TUNAthrough; Bruker Application Note #132 - Li, C.; Minne, S.; Pittenger, B.; Mednick, A.; Guide, M.; Nguyen, T.-Q.

PeakForce Kelvin Probe Force Microscopy; Bruker Application Note #140 - Li, C.; Minne, S.; Hu, Y.; Ma, J.; He, J.; Mittel, H.; Kelly, V.; Erina, N.; Guo, S.; Mueller, T.

(untitled) - Huang, Z.; De Wolf, P.; Poddar, R.; Li, C.; Mark, A.; Nellist, M. R.; Chen, Y.; Jiang, J.; Papastavrou, G.; Boettcher, S. W.; Xiang, C.; Brunschwig, B. S. (Microsc. Today, 2016)

(untitled) - Wang, L.; Wang, H.; Wagner, M.; Yan, Y.; Jakob, D. S.; Xu, X. G. (Sci. Adv., 2017)

(untitled) - Wang, H.; Wang, L.; Jakob, D. S.; Xu, X. G. (Nat. Commun., 2018)

(untitled) - Stan, G.; Gates, R. S. (Nanotechnology, 2014)

(untitled) - Xu, K.; Sun, W.; Shao, Y.; Wei, F.; Zhang, X.; Wang, W.; Li, P. (Nanotechnol. Rev., 2018)

(untitled) - Charrier, D. S. H.; Kemerink, M.; Smalbrugge, B. E.; de Vries, T.; Janssen, R. A. J. (ACS Nano, 2008)

(untitled) - Gramse, G.; Gomila, G.; Fumagalli, L. (Nanotechnology, 2012)

(untitled) - Xie, H.; Zhang, H.; Hussain, D.; Meng, X.; Song, J.; Sun, L. (Langmuir, 2017)

(untitled) - Jakob, D. S.; Wang, H.; Xu, X. G. (ACS Nano, 2020)

(untitled) - Hudlet, S.; Saint Jeana, M.; Guthmann, C.; Berger, J. (Eur. Phys. J. B, 1998)

(untitled) - Gil, A.; Colchero, J.; Gómez-Herrero, J.; Baró, A. M. (Nanotechnology, 2003)